MODEL PENANGANAN ANAK BERKONFLIK HUKUM - Yanuar Farida Wismayanti (Politeknik Kesejahteraan Sosial, 2007)
Arrest, detention or doing an injustice serve the child of conducted by legalistic goinginto effect and can only done by as last effort. The Jail, although however remain to prison. Study the model to handling the children conflict with the law in Surabaya city, East Java Province, showing its important a approach being based on community. Community Care the Child push the participation of society to handling the problem of children conflict with the law. Besides that the network of Child helpline consisted of by the local Non Government Organization, police and also related/relevant institution, proven to push the existence of support and its role in the effort cure and protection for children conflict with the law.Key words : Model, children conflict with the law.